The Economic Impact of the Affordable Care Act on Arkansas - Price, Carter C. (RAND Corporation, 2013)
The Affordable Care Act (ACA) will increase coverage through the expansion of Medicaid and the creation of a Health Insurance Exchange with subsidies. RAND researchers analyzed the ACA's economic impact on the state of Arkansas and found that by 2016, about 400,000 people will be newly insured, net federal payments to the state will amount to $430 million annually, and the total gross domestic product will see a net increase of $550 million.